Marine Bacteria Display Different Escape Mechanisms When Facing Their Protozoan Predators - Richard Guillonneau; Claudine Baraquet; Maëlle Molmeret (Microorganisms, 2020)
Free-living amoeba are members of microbial communities such as biofilms in terrestrial, fresh, and marine habitats. Although they are known to live in close association with bacteria in many ecosystems such as biofilms, they are considered to be major bacterial predators in many ecosystems. Little is known on the relationship between protozoa and marine bacteria in microbial communities, more precisely on how bacteria are able survive in environmental niches where these bacterial grazers also live. The objective of this work is to study the interaction between the axenized ubiquitous amoeba Acanthamoeba castellanii and four marine bacteria isolated from immersed biofilm, in order to evaluate if they would be all grazed upon by amoeba or if they would be able to survive in the presence of their predator. At a low bacteria-to-amoeba ratio, we show that each bacterium is phagocytized and follows a singular intracellular path within this host cell, which appears to delay or to prevent bacterial digestion. In particular, one of the bacteria was found in the amoeba nucleolar compartment whereas another strain was expelled from the amoeba in vesicles. We then looked at the fate of the bacteria grown in a higher bacteria-to-amoeba ratio, as a preformed mono- or multi-species biofilm in the presence of A. castellanii. We show that all biofilms were subjected to detachment from the surface in the presence of the amoeba or its supernatant. Overall, these results show that bacteria, when facing the same predator, exhibit a variety of escape mechanisms at the cellular and population level, when we could have expected a simple bacterial grazing. Therefore, this study unravels new insights into the survival of environmental bacteria when facing predators that they could encounter in the same microbial communities.